Some problems of the local textile millers related to finishing and their modernization plans /practices - Arsenue, Ruth Aldea; Ynchausti, Natividad S. (1992.)
This study is a documentary survey of some of the problems of local textile millers and their modernization plans/practices related to fabric finishing, with special focus on the basic special finishes. Dyeing and printing were not included in this study. Many of the previous studies and articles have mentioned some problems in the textile industry. This study focused on four factors/inputs that were frequently mentioned, such as, 1) machinery/equipment 2) raw material (chemicals) 3) staff/workers and 4) quality control system/procedures. Modernization plans/practices were also taken from the Textile Modernization Plans and Revised Textile Plans for 1989-1995. These information were then used to formulate which of the given problems the textile millers encountered most. Their modernization plans/practices were also given in these statements. The Likert scale, a 5-point scale in which spaces between the points are assumed to be equal with a set of related responses for each point, was then used for the questionnaire. A brief description on the respondent firms was also obtained such as 1) year started operations 2) classification 3) ownership, and 4) markets. There were only twelve respondents started to operate in the 50s and 70s. Four firms started to operate in the fifties and also four firms started to operate in the seventies. There integrated/specialized firms (3 firms). There was only one Chinese-owned firm, and the rest were Filipino-owned. The local market gets the biggest share of the local textile millers supply (respondent firms). Old firms encountered more problems than new firms and were also more conscious about their modernization especially in investing new machinery. Integrated firms which supply the three markets, local/direct export/indirect export, encountered the least problems compared to the other firms. The newer firms which supply the local market encountered more problems. Staff/workers and quality control were the two factors given greater importance by all respondent companies for modernization and even among the different groups. As an example, the staff/workers were encouraged to attend seminars for further training. In the aspect of quality control, some companies encourage Quality Circle groups to help solve coordinate with other problems in finishing. These companies also coordinate with other organizations or agencies for technical assistance in quality control.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Textile industry -- Philippines